Od porządkowania danych do Business Intelligence - jak uświadomiona wiedza staje się elementem konkurencyjności organizacji - Błotnicki, Andrzej; Wawrzynek, Łukasz (From data sorting to business intelligence - how the sensible knowledge becomes a component of the organization competitiveness, 2006)
This ailiclc regards the problem of usage of the information in terms of gathering the data in a company. The main purpose was to present a solution for an issue which is lack of ability and possibility of sensible outlooking and analyzing enormous amount of information which is stored as data. Tire introduced problem and the trial of solution refer mainly to small and medium enterprises as those have no access to the analytical tools which are very often loo expensive and moreover not exactly adjusted to company requirements
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 59-69